Efficacy of Some Selected Fungicides, Antibiotics and Sulphadrugs on the Radial Growth of Cercospora traversiana Sacc. Causing Leaf Spot/blight of Fenugreek (Trigonella foenum graecum linn.) - Nishant Mishra2, Chandra Pal Singh1*, U.S. Mishra1 and (Journal of Phytology, 2011)
Cercospora traversiana Sacc. was isolated from the leaves and pods of fenugreek (Trigonella foenum graecum Linn.). Five fungicides viz. Thiram, Dithane-M-45, Bavisin, Blitox and Vitavax, two antibiotics viz. Griseofulvin and Streptocycline and one sulphadrug viz. Sulphamethoxazole were studied in vitro against Cercospora traversiana. It was observed that the radial growth of pathogenic fungus was highly affected (95-100%) by Bavistin while other tested fungicides, antibiotics and sulphadrugs were moderately inhibited the radial growth of Cercospora traversiana. It is recommended that the leaf spot/blight of fenugreek can beÃ‚Â controlled successfully by the use of Bavistin (100ppm) as seed dressing system.